Blockchain Technology in Accounting Transforming Financial Reporting and Auditing - Fahdil, Husam Nawfal; Hassan, Hayder Mohammed; Subhe, Adel; Hawas, Abdulrazzaq Tuama (Journal of Ecohumanism, 2024)
Background: Blockchain technology is transforming numerous areas, including accountancy. Traditional financial reporting and auditing systems confront issues such as inefficiency, fraud risk, and a lack of transparency. Blockchain claims to solve these problems by implementing a decentralized, immutable ledger system. Objective: This study intends to investigate how blockchain technology can transform financial reporting and auditing. It aims to investigate how blockchain can improve transparency, accuracy, and security in accounting practices, as well as to assess the implications for auditors and stakeholders. Methods: A comprehensive literature study was undertaken to cover recent breakthroughs and applications of blockchain in accounting. This evaluation was supplemented with qualitative data from expert interviews with accounting professionals and blockchain specialists. Case studies of early blockchain adopters in accounting were also examined for empirical proof. A statistical examination of blockchain implementation outcomes was also undertaken utilizing data from 50 organizations that have integrated blockchain into their accounting operations. Results: The study found that blockchain technology enhances the trustworthiness and transparency of financial information. Blockchain's immutability minimizes the danger of data tampering and fraud, with 85% of studied businesses reporting a drop in fraudulent activity. Smart contracts and automated verification methods simplify auditing procedures, resulting in a 30% reduction in audit time and a 20% decrease in audit costs. Approximately 70% of organizations reported a 25% improvement in data accuracy, with 65% reporting a 40% gain in process efficiency. However, the report identifies several hurdles, including integration complexity, regulatory concerns, and the requirement for specialized skills. Approximately 60% of respondents identified regulatory difficulties as a major impediment to blockchain adoption, with 55% citing high initial implementation costs. Conclusion: Blockchain technology has the potential to improve transparency, security, and efficiency in financial reporting and auditing processes. While there remain barriers to widespread implementation, the benefits indicate that blockchain will play an important role in the future of accounting. Additional research and collaboration among stakeholders are required to address the problems and fully fulfill the technology's promise.